Politik Hukum Pidana terhadap Formulasi Sanksi Penggunaan Narkotika dalam Undang-Undang Nomor 35 Tahun 2009 Tentang Narkotika - Mukhtar Latif; Kholil Syuaib; Reza Iswanto; John Kennedy; Abdurahman Syayuthi; Jeki Noviardi; Dian Eka Putra (Wajah Hukum, 2026)
Problems arising in criminal law policy related to the formulation of sanctions for drug users in Law Number 35 of 2009 concerning Narcotics include the lack of clarity in distinguishing between addicts and dealers, inconsistent application of penalties, and the lack of a rehabilitation approach as an alternative to criminal punishment. This often results in users who should be receiving treatment being imprisoned, making it difficult to achieve the goals of recovery and reducing social impacts. Furthermore, there are challenges in integrating an understanding of international law and developments in health sciences with existing regulations in Indonesia. The research method applied uses a legislative approach with a six-month activity plan. The scope or object of study in this research includes criminal law policy and the establishment of criminal sanctions for drug abuse. The legal materials used consist of primary, secondary, and tertiary legal materials. The research location is focused on the Indonesian jurisdiction, with data collection techniques in the form of document studies. Data analysis was conducted using qualitative analysis methods. The results of this study are the problem in the regulation in Law Number 35 of 2009 concerning Narcotics regarding the use of narcotics is the application of harsh penalties for narcotics cases in Indonesia often does not clearly differentiate between users and dealers, so that many users who should receive rehabilitation are instead imprisoned and increasingly experience negative stigma. Law enforcement is also often inconsistent because the authorities have difficulty distinguishing users from dealers due to the unclear definition of narcotics in the regulations and criminal law politics regarding the formulation of sanctions for the use of narcotics in Law Number 35 of 2009 concerning Narcotics is directed at creating a balance between firm legal action to overcome narcotics abuse and providing rehabilitation opportunities for addicts in order to reduce the number of circulation, reduce negative impacts and save the younger generation from the dangers of narcotics more effectively and holistically.